Determinants of infant mortality in the Jequitinhonha Valley and in the North and Northeast regions of Brazil - Maria do Carmo Leal; Sonia Duarte de Azevedo Bittencourt; Raquel Maria Cardoso Torres; Roberta Pereira Niquini; Paulo Roberto Borges de Souza Jr
ABSTRACT OBJECTIVE This study aims to identify the social and demographic determinants, in addition to the determinants of reproductive health and use of health services, associated with infant mortality in small and medium-sized cities of the North, Northeast and Southeast regions of Brazil. METHODS This is a case-control study with 803 cases of death of children under one year and 1,969 live births (controls), whose mothers lived in the selected cities in 2008. The lists of the names of cases and controls were extracted from the Sistema de Informação sobre Mortalidade (SIM - Mortality Information System) and the Sistema de Informação sobre Nascidos Vivos (SINASC - Live Birth Information System) and supplemented by data obtained by the research of "active search of death and birth". Data was collected in the household using a semi-structured questionnaire, and the analysis was carried out using multiple logistic regression. RESULTS The final model indicates that the following items are positively and significantly associated with infant mortality: family working in agriculture, mother having a history of fetal and infant losses, no prenatal or inadequate prenatal, and not being associated to the maternity hospital during the prenatal period. We have observed significant interactions to explain the occurrence of infant mortality between race and socioeconomic score and between high-risk pregnancy and pilgrimage for childbirth. CONCLUSIONS The excessive number of home deliveries and pilgrimage for childbirth indicates flaws in the line of maternity care and a lack of collaboration between the levels of outpatient and hospital care. The study reinforces the need for an integrated management of the health care networks, leveraging the capabilities of cities in meeting the needs of pregnancy, delivery and birth with quality.